2012
DOI: 10.1089/aid.2011.0390
|View full text |Cite
|
Sign up to set email alerts
|

Phylodynamic and Phylogeographic Patterns of the HIV Type 1 Subtype F1 Parenteral Epidemic in Romania

Abstract: In the late 1980s an HIV-1 epidemic emerged in Romania that was dominated by subtype F1. The main route of infection is believed to be parenteral transmission in children. We sequenced partial pol coding regions of 70 subtype F1 samples from children and adolescents from the PENTA-EPPICC network of which 67 were from Romania. Phylogenetic reconstruction using the sequences and other publically available global subtype F sequences showed that 79% of Romanian F1 sequences formed a statistically robust monophylet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…Ten of the 49 HIV participants had previous HIV clade evaluation (due to virological failure); all had F1 HIV subtype. Furthermore, previous molecular demographic and phylogeographic analyses (Mehta et al 2011; Mbisa et al 2012) demonstrated that F subtype was responsible for the Romanian nosocomial pediatric HIV epidemic. Participants were excluded if they were unable to provide informed consent, had a neurocognitive morbidity unrelated to HIV condition (e.g., recent and/or significant traumatic brain injury, color blindness, hearing deficit that appears to affect auditory comprehension, neurosyphilis, stroke, etc.…”
Section: Methodsmentioning
confidence: 92%
“…Ten of the 49 HIV participants had previous HIV clade evaluation (due to virological failure); all had F1 HIV subtype. Furthermore, previous molecular demographic and phylogeographic analyses (Mehta et al 2011; Mbisa et al 2012) demonstrated that F subtype was responsible for the Romanian nosocomial pediatric HIV epidemic. Participants were excluded if they were unable to provide informed consent, had a neurocognitive morbidity unrelated to HIV condition (e.g., recent and/or significant traumatic brain injury, color blindness, hearing deficit that appears to affect auditory comprehension, neurosyphilis, stroke, etc.…”
Section: Methodsmentioning
confidence: 92%
“…Given the particular local spread of a non-B subtype in Galicia initially described by Thomson et al (2012), we looked into more detail at the characteristics of the HIV-1 epidemic in Galicia by means of molecular epidemiological analyses. We used a large collection of samples from two major cities and by using current state of the art methods for phylogeographic and phylodynamic analyses we estimated the origin and the transmission dynamic for subtype F. Given the rarity of subtype F in Europe, where Romania is the only endemic area, the monophyletic clustering of subtype F (Apetrei et al, 1997;Apetrei et al, 1998;Bandea et al, 1995;Mbisa et al, 2012 ;Mehta et al, 2011), which is indicative of local transmission, is not surprising. This is can be explained due to the low frequency of this subtype in western countries, from where we expect that the local population in Galicia retains most contacts.…”
Section: Discussionmentioning
confidence: 99%
“…However, an increasing trend of subtype F among MSM has recently been identified in Galicia, Northwest of Spain (Thomson et al, 2012). Subtype F has since been detected in Romania in Europe, as well as in Africa and Brazil (Anta et al, 2013;Apetrei et al, 1997;Apetrei et al, 1998;Bandea et al, 1995;Louwagie et al, 1994;Mbisa et al, 2012 ;Mehta et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Unrelated to the Brazilian epidemic, sub-subtype F1 was initially introduced and spread among adult heterosexuals in Romania. In this Eastern-European country, it subsequently reached a very high prevalence rate of more than 70% due to several major outbreaks among children in orphanages and people using intravenous drugs (Dumitrescu et al, 1994; Bandea et al, 1995; Apetrei et al, 1998; Op De Coul et al, 2000; Guimarães et al, 2009; Paraschiv et al, 2009; Mehta et al, 2011; Mbisa et al, 2012; Niculescu et al, 2014). Both Brazil and Romania were at the origin of the F1 epidemic in Italy, where Brazilian strains contributed to many more introduction events characterized with a more extensive spread (Lai et al, 2014).…”
Section: Discussionmentioning
confidence: 99%